1990
DOI: 10.1093/ije/19.1.115
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Injuries in Young People: I Methodology and Results of a Collaborative Study in Brazil, Chile, Cuba and Venezuela

Abstract: Injuries and accidents are acknowledged as leading causes of mortality among children and adolescents in the developing countries of the world. However, little is known of the extent of non-fatal injuries and of their potential risk factors. The Pan American Health Organization sponsored the first collaborative study to examine morbidity incidence in specified areas of four selected countries in Latin America, and to test the feasibility and practicality of the developed methodology for application in other re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1
4

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 0 publications
4
30
1
4
Order By: Relevance
“…Most studies of distribution of injury in a population focus on hospital admissions or attendances (Zwi 1993). Hospital-based rates of injury are much lower than those based on community survey (Bangdiwala et al 1990). In the Ghanian series, the rate of serious injuries in a rural population requiring hospital admission was 0.6/1000 persons per year (Mock et al 1995).…”
Section: Distribution Of Mortality ----------------------------------mentioning
confidence: 86%
“…Most studies of distribution of injury in a population focus on hospital admissions or attendances (Zwi 1993). Hospital-based rates of injury are much lower than those based on community survey (Bangdiwala et al 1990). In the Ghanian series, the rate of serious injuries in a rural population requiring hospital admission was 0.6/1000 persons per year (Mock et al 1995).…”
Section: Distribution Of Mortality ----------------------------------mentioning
confidence: 86%
“…Sexo masculino, baixo nível socioeconômico, presença de dois ou mais irmãos e cuidado da criança pela mãe, em alguns estudos em países desenvolvidos 5,6 e em desenvolvimento [7][8][9] , têm sido apontados como alguns dos principais fatores de risco para injúrias acidentais. Outros estudos, porém, não encontraram esta relação 10,11 .…”
unclassified
“…Home injuries mainly affected children (0 -14 years old) and old people (60 years and above). Bangdiwala et al (1990) also showed that the home was the most frequent (37 -57%) setting for injuries, especially for the young (16). Home injuries stand out as dominant in both frequency and severity, and our findings suggest that greater attention needs to be directed toward the prevention of injuries occurring in the home in rural Vietnam.…”
Section: Discussionmentioning
confidence: 50%
“…Latin American injury studies combined institutional recording with household surveys and found 60 injuries/1,000 people/year in Cuba, 220 in Venezuela and 303 in Chile (16). An American National Health Survey in 1979, which included questions on injuries, found 345 injuries/1,000/year (17).…”
Section: Discussionmentioning
confidence: 99%